Formulation of Bitumen from Industrial Waste - Mohd Najib, Razali; M. Luqman Hakim, M. Effendi; Musfafikri, Musa; R. M., Yunus (2015)
Bitumen is a mixture of organic liquids which is black, high viscosity and it is sticky materials where it can be applied in several of application. Waste sludge can be used as another alternative to formulate the bitumen by manipulating ratio needed. Waste sludge consists of mineral oil solid waste, which includes oily sand, tank bottoms and other three kinds of sludge from refineries such as dissolved air flotation scum, excessively activated oily sludge and bottom sludge of oil from pools. Waste sludge is the major source of pollution produced in the process of oilfield production and development. In order to formulate the bitumen, other material that is needed include mineral oil, waste sludge and crumb rubber. The form of crumb rubber is form from discarded tyre. Generally, the tyre rubber is ground to a particulate or crumb prior to adding it to bitumen. This form of the tyre rubber is called Crumb Rubber and the mineral oil is used as the medium to heat up the crumb rubber until it is melt and dissolved. The main objective in this experiment is to formulate and identify the best ratio of the bitumen produced. The method that is used to formulate is heating and mixing process which is being conducted inside the fume hood. So that it can absorb the fume released when the process is conducted. The key parameter during the process is weight of the sample, temperature, time and the speed of the mixer (rpm). Once it is produced, then the sample need to analyse based on the density 15°C using ASTM D70 method, viscosity test by using ASTM D2170, penetration @ 25°C test which by using ASTM 5 method and softening point test which is by using ASTM D36 method. The best ratio by far is (1:2:1.2) formulation by having viscosity of 93 centipoise, density of 1.0398 Kg/L, softening point which is at 62°C and penetration which is at >40 mm of penetration. The sample that is formulated were then being compared with the actual bitumen sample